Achieving reliable pain change scores for individuals in the postoperative phase: carefully choose sampling density, test length, and administration mode. Issue 1 (7th January 2022) - Obbarius, Alexander; Schneider, Stefan; Junghaenel, Doerte U.; Stone, Arthur A.
Abstract : Supplemental Digital Content is Available in the Text. Several factors can influence the reliability of change scores obtained in the postoperative period, including test length, sampling density, mode of assessment, and the individual item. Our findings suggest that these factors should be considered when planning the postoperative assessment of pain measures. Abstract: Despite tremendous efforts to increase the reliability of pain measures and other self-report instruments, improving or even evaluating the reliability of change scores has been largely neglected. In this study, we investigate the ability of 2 instruments from the Patient-Reported Outcomes Measurement Information System, pain interference (6 items) and pain behavior (7 items), to reliably detect individual changes in pain during the postsurgical period of a hernia repair in 98 patients who answered daily diaries over almost 3 weeks after surgery. To identify the most efficient strategy for obtaining sufficiently reliable estimates of change (reliability >0.9), the number of measurement occasions over the study period (sampling density), the number of items (test length), and the mode of administration (ie, static short form vs Computer adaptive testing) were manipulated in post-hoc simulations. Reliabilities for different strategies were estimated by comparing the observed change with the best approximation of "real" (ie, latent) change. We found (1) that near perfect reliability can be achieved if measures from all days over the whole study period, obtained with all pain interference or pain behavior items, were used to estimate the observed change, (2) that various combinations of the number of items and the number of measurement occasions could achieve acceptable reliability, and (3) that computer adaptive testings were superior to short forms in achieving sufficient reliability. We conclude that the specific strategy for assessing individual postoperative change in pain experience must be selected carefully.